Remains of the church (16100303559) - Miami University... (Wikimedia Commons, 2015)
Carte postale ancienne issue de Wikimedia Commons. Titre: Remains of the church (16100303559). Persistent URL: digital.lib.miamioh.edu/cdm/compoundobject/collection/pos... Subject: World War I | Lost architecture | France--Pareid | miami digital collections | bowden postcard collection
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale